The The Influence Of Green Awareness, Green Products, And Green Pricing On Purchase Decision For Fast Moving Consumer Goods, With Green Lifestyle As Mediating Variabel : (A Study On Generation Z In South Jakarta) - Almira; Awang Darmawan Putra (Program Studi Ilmu Administrasi Bisnis FISIP UNPAS, 2026)
The aim of this study is to analyse the influence of green awareness, green products, and green price, mediated by green lifestyle on consumer purchase decision of FMCG personal care products among Generation Z of South Jakarta. This study utilizes quantitative approach with multiple regression analysis methods and mediating testing. The sample consists of 196 generation Z respondents residing in South Jakarta. This study finds Green awareness, green product, and green price positively affect consumer purchase decisions. Green lifestyle mediates green products and green price positive influence on consumer purchase decision. Green awareness does not have a direct influence once green lifestyle is included as a mediator. In conclusion adopting a green lifestyle is necessary to achieve consumer purchase decision, green product is proven to have the strongest influence out of all three independent variables